Integration-free Methods for Generating Induced Pluripotent Stem Cells - Zhou, Yi-ye (Genomics Proteomics Bioinformatics, 2013)
Induced pluripotent stem (iPS) cells can be generated from mouse or human fibroblasts by exogenous expression of four factors, Oct4, Sox2, Klf4 and c-Myc, and hold great potential for transplantation therapies and regenerative medicine. However, use of retroviral vectors during iPS cell generation has limited the technique’s clinical application due to the potential risks resulting from genome integration of transgenes, including insertional mutations and altered differentiation potentials of the target cells, which may lead to pathologies such as tumorigenesis. Here we review recent progress in generating safer transgene-free or integration-free iPS cells, including the use of non-integrating vectors, excision of vectors after integration, DNA-free delivery of factors and chemical induction of pluripotency.